Long-Term Rugby Player Development: Strategies & Complications: A Review - Gimhan, B. M.; Mayakaduwa, U. T.; Chandana, A. W. S. (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
Long-term player development in rugby is a complex process that involves physical, technical, tactical, and mental growth. This progression follows structured models like the Long-Term Athlete Development (LTAD) framework. Key factors for maximizing a player’s potential over time include learning basic movement skills at a young age, age- appropriate sport-specific training, structured training phases, and strength and conditioning programs tailored to different playing positions. Starting with multiple sports rather than specializing too early helps players develop a strong foundation of motor skills while reducing injury risks. This well-rounded approach benefits both their physical and mental development, leading to better long-term performance. However, implementing LTAD effectively in rugby comes with several challenges. Early specialization increases the risk of burnout and injuries, especially since young athletes’ bodies are still growing.   To understand these challenges, a systematic review was conducted using various online databases. Out of 30 relevant sources, 25 were journal articles, one was a book, two were federation modules, and two were grey literature sources. Given rugby’s high-contact nature, injuries are common. Programs like World Rugby’s Activate initiative are strongly recommended to help reduce the occurrence of concussions, ligament injuries, sprains, and muscle strains. Another major challenge is player retention, particularly during transitions from youth to senior levels. Many young players drop out due to unrealistic expectations, increased pressure, and a lack of proper support. Socio-economic and geographical barriers also play a significant role. Players from underprivileged backgrounds often have limited access to quality coaching and training facilities. To address these issues, rugby needs more inclusive pathways, fair distribution of resources, and innovative solutions like wearable technology to monitor player workload and optimize training. This review highlights the importance of personalized development plans, ongoing injury prevention strategies, and increased access to rugby opportunities. Future research should focus on refining LTAD models, creating standardized evaluation tools, and developing adaptable, evidence-based training programs to ensure sustainable and equitable player development.